Доля чернігівського Спасо-Преображенського собору за часів міжконфесійного протистояння у 20-х рр. ХХ ст. - Ванжула, О. (Сiверянський лiтопис, 2017)
Стаття присвячена маловивченому періоду з історії чернігівського Спасо-Преображенського собору —20-м рр. ХХ ст. Розглянуті питання міжконфесійного протистояння між протиборчими православними громадами, майнові та правові аспекти боротьби за церковне майно чернігівських кафедральних соборів на тлі антирелігійної
державної політики радянської влади. Статья посвящена малоизученному периоду в истории черниговского Спасо-Преображенского собора — 20-м гг. ХХ в. Рассмотрены вопросы межконфессионального
противостояния между противоборствующими религиозными общинами, имущественные и правовые аспекты борьбы за церковное имущество черниговских кафедральных
соборов на фоне антирелигиозной государственной политики советской власти. The article reveals the history of the Cathedral of the Transfiguration of Our Saviour in
Chernihiv during the 1920’s. The dramatic changes of social order of the country occurred at that period of national history, stereotypes and sustainable lifestyle, closely connected with the Orthodox Church, were
ruined. Since its inception the Bolshevik government declared freedom of belief and respect
for the religious feelings of citizens. However, it actually started the unstoppable attack on
the church, which was its main ideological opponent, that concentrated of a lot of wealth in
its hands. The traces of complex social processes during 1920’s are discovered throughout the
whole history of the ancient cathedral in Chernihiv. For centuries the Cathedral of the Transfiguration of Our Saviour and Ss. Boris and Hlib Cathedral were the main churches of the eparchy, which played a leading communicative and sacred role. In 1919 a powerful Orthodox Parish-Community was organized at the Cathedral
of the Transfiguration of Our Saviour, which included more than 2,000 faithful.
During the 1919-1921 the government launched a process of registration of Orthodox
communities as well as identifying and accounting church property and values.
Subsequently, this led to the mass seizure of church valuables – famine in the Volga River
region of 1921-1923, that turned into a real robbery of the Orthodox Church and caused a
church split. In this period the final formation of renovationism occurred. This movement was
born on the border of the nineteenth and twentieth centuries, when life of the Russian Orthodox
Church (hereinafter – ROC) began to emerge obvious signs of institutional crisis that led to
the spread among the clergy idea of a «renewal» of the church. In the wake of these ideas were
created Ukrainian Autocephalous Orthodox (hereinafter – UAOC) and Renovated Church.
In 1921 the government gave Ss. Boris and Hlib Cathedral to the newly created community
of UAOC in Chernihiv. This caused the rise of an acute confrontation and struggle with the
community of ROC. The Soviet government successfully used the struggle and internal conflicts
in the clerical community to finally discredit and split the church as a social institution.
Since 1923 at the Cathedral of the Transfiguration of Our Saviour acted the renovation
community. During the 1925-1926 in this cathedral were recorded Old Slavonic (Tikhon) and
Synodal (renovative) communities, which were in conflict with each other.
However, renovationism had no prospects for its further development due to extremely
robust tradition of canonical Orthodoxy among the believers of the Chernihiv gubernia and
city, and its support by the Soviet authorities was planned as a temporary measure to deal with
more powerful Russian Orthodox Church. Ideologically, no religious denomination fit into the
overall concept of strong ateisation of the country and was doomed to destruction.
The reason for the mass break agreements with religious communities in the late 1920’s was
lack of repair and poor maintenance of places of worship, as the Bolsheviks had destroyed the
material basis of the Church. The punitive power system joined to the physical destruction of
clergy loyal to the government as well as opposition. Finally, on May 18, 1927, according to the decision of Council of People’s Commissars of USSR buildings of the Cathedral of the Transfiguration of Our Saviour, the Dormition (Uspensky) and St. Trinity Cathedrals in Chernihiv were declared historical and architectural
monuments of nationwide significance and transferred to the jurisdiction of the People’s Commissariat
of Education. Thus, the Cathedral of the Transfiguration of Our Saviour, became a museum reserve.